2017
DOI: 10.1002/mrc.4615
|View full text |Cite
|
Sign up to set email alerts
|

Determining the relative strengths of aromatic and aliphatic C―H⋅⋅⋅X hydrogen bonds in imidazolium ionic liquids through measurement of H/D isotope effects on 19F nuclear shielding

Abstract: The relative strengths of aromatic and aliphatic C-H⋅⋅⋅X hydrogen bonds in imidazolium ionic liquids were investigated through measurement of H/D isotope effects on the F nuclear shielding of deuterated isotopologues of 1-n-butyl-3-methylimidazolium hexafluorophosphate and tetrafluoroborate ([C mim]PF and [C mim]BF ). Δ F(H,D) values ranging from 9.7 to 49.7 ppb were observed for [C mim]PF isotopologues, while for the [C mim]BF series these went from 26.2 to 83.8 ppb. Our findings indicate that the interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…The 1:1:1 triplet expected for the CD carbon of the deuterated methylimidazolium ion was not observed in the recorded 13 C NMR spectra, presumably because 400 MHz instruments are insufficiently sensitive, and the signal is broadened by coupling and exchange. Earlier studies also reported deuteration of imidazolium cations in deuterated solvents in the presence of a Brønsted basic anion. , …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The 1:1:1 triplet expected for the CD carbon of the deuterated methylimidazolium ion was not observed in the recorded 13 C NMR spectra, presumably because 400 MHz instruments are insufficiently sensitive, and the signal is broadened by coupling and exchange. Earlier studies also reported deuteration of imidazolium cations in deuterated solvents in the presence of a Brønsted basic anion. , …”
Section: Resultsmentioning
confidence: 94%
“…Earlier studies also reported deuteration of imidazolium cations in deuterated solvents in the presence of a Brønsted basic anion. 17,18 Scalar or J Coupling. 1 H NMR chemical shifts are recorded alongside their multiplicities and coupling constants to aid the identification of unknown impurities.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…This reaction has been widely used to evaluate protein dynamics in water and, more recently, has been extended to organic compounds and ILs. 27,42 The rate at which these protons exchange is usually determined by their participation in hydrogen bonds and by their surface exposure. 43 Herein, the BMMIÁX was dissolved in CDCl 3 and 1 H NMR S7-S9).…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26] Recently, Moyna and co-workers demonstrated the relative strengths of aromatic and aliphatic C-HÁ Á ÁX hydrogen bonds in deuterated ImILs through the measurement of H/D isotope effects on 19 F nuclear shielding. 27 In a similar study they suggested the use of their methodology in future efforts to study host-guest complexes and other systems where these weak interactions are present. 28 Since ILs are often used in conjunction with other solvents or have small amounts of water, it is valuable to understand the nature of the ion-solvent interaction.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, H-bonds in ILs and IL-based systems have been investigated using NMR (10), IR and Raman spectroscopy (11)(12)(13), X-ray crystallography (14)(15)(16), and neutron diffraction (17). More recently, we have also shown that secondary H/D isotope effects on nuclear shielding (IENS) can be employed to investigate H-bonds in N,N'-dialkylimidazolium salts (18)(19)(20). This conceptually simple methodology relies on the chemical shift perturbation suffered by NMR-active nuclei of an H-bond acceptor group upon H/D replacement on the donor group (21).…”
Section: Introductionmentioning
confidence: 99%